Narratives of trauma, recovery, and growth: The complex role of sport following permanent acquired disability. (January 2016) - Day, M.C.; Wadey, R.
Abstract: Objectives: The purpose of this study was to explore how participation in sport may assist an individual in working through experiences of physical trauma. Design: An instrumental, collective case study was used to illustrate the experiences of two men with acquired disabilities. Method: Both men participated in sport at a high level and suggested that participation was a central feature of their recovery from trauma. Interviews invited participants to describe their lives pre-trauma, the trauma experience, and the recovery process. A narrative analysis was used to focus on the progression of the plot outlined in each participant's story. Results: Our results exemplify two narrative types: assimilation and positive accommodation. The narrative of positive accommodation demonstrates how sport provided mastery experiences, enhanced relationships, corporeal understanding and enhanced life philosophies. The alternative narrative of assimilation was associated with resilience to trauma. Our case illustrates that such a narrative may be focused on re-capturing previous life meanings and creating an athletic identity using past definitions of sport. Conclusion: While the narrative of positive accommodation is most frequently associated with posttraumatic growth, our case outlines the occurrence of synchronous positive and negative experiences, even within the same dimensions of growth. The narrative of assimilation demonstrates the challenges presented by the rehabilitation and sporting environments for an individual who aimed to restore their pre-trauma self and pre-trauma beliefs. Highlights: We examine the role of sport in recovery and growth from physical trauma. Two narrative types are illustrated: assimilation and positive accommodation. Positive accommodation focused on mastery and corporeal understanding. Assimilation focused on re-capturing previous life meanings.